2008
DOI: 10.1038/sj.jid.5701188
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes Stimulates Pro-Matrix Metalloproteinase-2 Expression through Tumor Necrosis Factor-α in Human Dermal Fibroblasts

Abstract: Propionibacterium acnes (P. acnes) is a commensal microorganism found in sebum-rich skin and plays a role in acne inflammation by stimulating keratinocyte to produce a number of proinflammatory cytokines. However, the role of P. acnes in the dermis of acne lesions, where tissue remodeling after inflammation eventually takes place, is not known. In this study, we investigated whether P. acnes induces matrix metalloproteinase (MMP), a key enzyme involved in matrix remodeling in human dermal fibroblasts (hDF). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 43 publications
(46 reference statements)
3
53
0
4
Order By: Relevance
“…In an effort to establish a relationship between diagnostic/prognostic optical techniques and laser–tissue interactions, we have employed the rodent dorsal window-chamber model as an in vivo platform19,25,30,76 to evaluate phototherapies designed to eliminate aberrant blood vessels. Based on data collected from over 300 experiments, it was shown that, in the absence of complete acute photocoagulation of the irradiated vessels, the laser-irradiated region of interest (ROI) remains perfused.…”
Section: Combined Laser Treatment and Optical Imagingmentioning
confidence: 99%
“…In an effort to establish a relationship between diagnostic/prognostic optical techniques and laser–tissue interactions, we have employed the rodent dorsal window-chamber model as an in vivo platform19,25,30,76 to evaluate phototherapies designed to eliminate aberrant blood vessels. Based on data collected from over 300 experiments, it was shown that, in the absence of complete acute photocoagulation of the irradiated vessels, the laser-irradiated region of interest (ROI) remains perfused.…”
Section: Combined Laser Treatment and Optical Imagingmentioning
confidence: 99%
“…Using gene array expression profiling, Trivedi et al13 reported that most of the genes dysregulated in acne are involved in the inflammation and extracellular matrix remodeling pathways. Choi et al14 have shown that the expression of proMMP-2 is induced by P. acnes through the nuclear factor-kappa B pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the previous studies doxycycline was shown to inhibit phosphorylation and nuclear translocation of the NF-kB-p65 and NF-kB-induced MMP-9 expression in lung cancer cell migration and invasion [41]. In another study in human dermal fibroblasts doxycycline inhibited TNF-a--induced NF-kB-mediated MMP-2 expression but not MMP-9 expression [46]. Consistently with the results of these studies, we observed that inhibition of MMP-9 and -8 expression by doxycycline was associated with the down-regulation in the expression of NF-kB/p65, IKK-b and the reduction in the phosphorylation of IkB-a in PC3 prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%